PENINGKATAN KOMPETENSI GURU DALAM RANGKA MEWUJUDKAN GURU YANG PROFESIONAL - Ibadullah Malawi (Universitas PGRI Madiun, 2011)
Teachers as professional educators are obliged to plan and excute learning process, to evaluate outcomes, to give advice, to train, to develop studies, to support school deveopment program and to develop professionalism. Among other criteria, professional teachers must master learning materials, develop educating learning process, have good personality and build commitment of students’ learning skill. To make them competent in conducting all of those tasks, teachers must have ability to search for information from variety of resources and from research which they conduct to support their educating instruction.